Clinical Utility of Fluid Volume Assessment in Heart Failure Patients Using Bioimpedance Spectroscopy - Accardi, Andrew J.; Matsubara, Bradley S.; Gaw, Richelle L.; Daleiden-Burns, Anne; Heywood, James Thomas (Frontiers in Cardiovascular Medicine, 2021)
Background Bioimpedance spectroscopy (BIS) is a noninvasive method used to measure fluid volumes. In this report, we compare BIS measurements from patients with heart failure (HF) to those from healthy adults, and describe how these point-of-care fluid volume assessments may be applied to HF management. Methods and Results Fluid volumes were measured in 64 patients with NYHA class II or III HF and 69 healthy control subjects. BIS parameters including extracellular fluid (ECF), intracellular fluid (ICF), total body water (TBW), and ECF as a percentage of TBW (ECF%TBW) were analyzed. ECF%TBW values for the HF and control populations differed significantly (49.2 ± 3.2% versus 45.2 ± 2.1%, respectively; p < 0.001); both distributions satisfied criteria for normality. Interquartile ranges did not overlap (46.7 to 51.0% versus 43.8 to 46.4%, respectively; p < 0.001). Subgroup analyses of HF patients who underwent transthoracic echocardiography showed that impedance measurements correlated with inferior vena cava size (Pearson correlation -0.73, p < 0.0001). A case study is presented for illustrative purposes. Conclusions BIS-measured ECF%TBW values were significantly higher in HF patients as compared to adults without HF. We describe three strata of ECF%TBW (normal, elevated, fluid overload) that may aid in clinical risk stratification and fluid volume monitoring of HF patients.